Non-standard use and successful implementation of I2C protocol for a temperature measurement system in high altitude Andean small towns - Palomino Masco, Joel Fernando (2020)
This article describes the design and development of a compact low energy consumption temperature data acquisition system using the I2C protocol with cables up to eight meters long. This system has been used in the implementation of a Peruvian government project aimed at validating the use of Trombe walls in small towns located at high altitude (4000 - 5000 m.a.s.l.). This article explains the construction of the module, the data acquisition subsystem, and presents an overview of the implementation of the developed system.